Mobilização precoce de pacientes criticamente doentes: ensaio clínico aleatorizado - Rodrigo Cesar Maia Moreira (2012)
Context. Investigations of physiotherapy applied to intensive care have focused attention on the early management of critically ill patients, aimed at decisionmaking to minimize the complications inherent in the admission and treatment of primary disorders related to long periods of bed rest. Purpose. To evaluate the applicability of a protocol the early mobilization to facilitate the exit of bed for patients in intensive care unit. Method. Randomized clinical trial carried out in hospital Risoleta Tolentino Neves / MG. Patients were randomized into two groups(treatment - control and n = 67 - n = 67). The groups were compared based on age, gender, lactate, Acute Physiology and Chronic Health Evaluation II, C-reactive protein, duration of mechanical ventilation and diagnosis. The control group was accompanied throughout the length of stay by the physiotherapy team from the usual care and the treatment group, beyong that follow was submitted to the proposed protocol. The protocol was initiated from 24 hours after admission and consisted of four stages of activities in accordance with the level of awareness andstrength in upper and lower limbs which was also used as parameter ofprogression. All variables were submitted to Kolmogorov Smirnov test for normality and subjected to Mann Whitney U and chi-square test. Results. The characteristics of the groups were similar at baseline. Of the total 134 patients, there were 14 exclusions (7 in the treatment group and 7 in control) due to complications during hospitalization. There were two adverse events attributed to the protocol, and a loss of peripheral venous access and a loss of nasoentérica probe. The proportion of patients who left the bed was different between groups, 61 patients in the treatment group and only two in the control (p = 0.001). The length of stay in ICU was 264.76 hours vs. 379.71 hours (p = 0.122) in the treatment and control groups, respectively. There was no statistically significant difference between groups in length of hospital stay, the treatment group had an average of 28.6 days of hospitalization (95% CI - 21.37 to 35.83) days, while the control had an average of 36, 1 (95% CI - 28.04 to 44.13) (p = 0.159). The treatment group had a mean duration of mechanical ventilation was 5.36 (95% CI - 3.32 to 7.40) days while the control group had an average of 7.66 (95% CI - 5.09 to 10, 22) days (p = 0.094). In this study, the ICU mortality reached 18.7% (25 patients) was not statistically different between groups (p = 0.506), maintaining the same standard, the mortality rate was 26.1% (35 patients) (p = 0.844). The average cost for each hour of admission recorded by HRTN abril-setembro/11 the period was R $ 55.70 / patient, taking into account the length of stay (hours) ICUtreatment group was responsible for R $ 14,746 , 28 average / patient while the control group was responsible for R $ 21,148.62 average / atient (p = 0.122). Conclusion. The findings of this survey were similar to previous studies and demonstrate that early mobilization is safe, effective and encourages early exit from the bed, especially when initiated after 24 hours of ICU admission. Early mobilization was clinically relevant in all contexts, reducing the time of ICU admission, as well as their total costs.